Transient wave-based methods for anomaly detection in fluid pipes: A review. (November 2021) - Che, Tong-Chuan; Duan, Huan-Feng; Lee, Pedro J.
Highlights: Comprehensive review on the transient wave-based methods for pipe anomaly detection. Systematical introduction on the fundamental physics and mechanism of transient wave propagation in fluid pipes. Summary on the typical signal processing and feature extraction techniques for the transient wave-based methods. Elaboration on the detection principles, advances, advantages, and disadvantages of five typical anomaly detection methods. Discussion of the challenges and future work on the reviewed topic, in association with research recommendations. Abstract: Over the years, anomaly detection of fluid pipes has been a focus of water authorities as well as oil and gas operators to advance the operation and management of these mechanical systems. This paper presents a comprehensive review on the development and application of transient wave-based methods for the detection of different anomalies in fluid pipes. A brief introduction of the fundamental physics and mechanism of transient waves in both intact and defective pipes is first presented. Different techniques and principles for transient wave generation and measurement are then discussed. In addition, the signal processing techniques commonly used for feature extraction from the measured signals are summarized. The main focus of this paper is on the comprehensive review of the technological advances and characteristics of five common types of transient wave-based anomaly detection methods for fluid pipe systems, namely (1) reflection-based method; (2) damping-based method; (3) FRF peak pattern-based method; (4) time domain full-waveform inversion method; and (5) frequency domain full-waveform inversion method. Afterwards, two practical applications of transient wave-based methods for anomaly detection in real-life fluid pipe systems are introduced and discussed. Finally, recommendations for future work in this research field are given.